PENGGUNAAN MODEL PEMBELAJARAN KREATIF TERHADAP KEMAMPUAN MAHASISWA DALAM BELAJAR WACANA BAHASA INDONESIA MAHASISWA SEMESTER V - Robiyatul Adawiyah (Linguistik : Jurnal Bahasa dan Sastra, 2021)
The purpose of this study was to describe the results of the use of creative learning models on students' abilities in studying Indonesian language discourse for semester V students. This research used a qualitative descriptive method. With the number of research samples 25 students. The research was carried out for Â± 4 months from November to February 2021. Based on the results of the research, it was found that 98% of 100% of learning outcomes using creative learning models increased students' abilities in learning Indonesian language discourse for fifth semester students. It can be seen from the average score of students who have reached 89 in the "good" category.